Improvement of koye kacang powder forming machine - Shamsudin, Rosnah; Zainuddin, Muhammad Fakhri; Ibrahim, Nur Athirah; Mohd Adzahan, Noranizan; Ramli, Noor Azwani (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2014)
“Koye Kacang Powder Forming Machine” (PI 2010004452) was introduced to alleviate the burden of local cookie suppliers in the mass production of “kuih koye” or nut cookies for Hari Raya Shoppers. Generally, “kuih koye” is still being produced in the traditional way. It is a concoction of slightly damp grinded green beans and sugar, pressed into a wooden mould with shapes according to one’s own personal interest. This traditional method however is time consuming, requires high labour costs, and produces low yields. “Koye Kacang Powder Forming Machine” was invented to aid the needs of local 'kuih koye' suppliers. It is hassle-free and easy to operate. Based on a series of performance testings, it was deemed as a perfect alternative to the traditional method. The footprint of the machine is 1570mm x 668mm with the height of 1800mm. The machine comprises of pneumatic, compression cylinder, upper moulds made of food grade silicone, centre plate with wells, and lower collecting tray. The mechanisms involved are the powdered mixture filling, compression process and finally cookie collection. The powdered ingredients are loaded manually into the automatic filling module. Then, the concoction will automatically be swept into the wells just above the collecting tray followed by a compaction by upper moulds. The whole process ends when the upper moulds were lifted up and 'kuih koye' were seen readily available for the final step which is, drying. However, due to several glitches observed, such as the uneven shapes of 'kuih koye' after the compaction process, certain measures were taken and improvements have been made to the machine. The food grade silicone moulds were replaced with food grade polyurethane (PE) moulds. In a nutshell, this innovation reduces human error, labour costs, and time consumption. In terms of the quality, it is on par with the traditional method of making 'kuih koye'.